2017
DOI: 10.1109/tnsre.2017.2740945
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Validity of Discriminating Yaw Plane Head-on-Trunk Motion Using Inertial Wearable Sensors

Abstract: A consequence of vestibular loss is increased coupling of head-on-trunk motion, particularly in the yaw plane, which adversely affects community mobility in these patients. Inertial sensors may provide a means of better understanding normal decoupling behaviors in community environments, but demonstration of their validity and responsiveness is needed. This paper examined the validity and measurement sensitivity of inertial sensors in quantifying yaw plane head-trunk decoupling during unrestricted and restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…Previous studies of prescribed head movements during gait activities in individuals post-mTBI have, in most cases, limited their focus to yaw plane head rotations. Similarly, studies examining head rotation kinematics during dynamic tasks in other vestibular-impaired populations have primarily focused on yaw plane directed head movements 5,15,17,28. Our findings extend the results of these studies by confirming that head velocity alterations are not plane specific and may share a common mechanism.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Previous studies of prescribed head movements during gait activities in individuals post-mTBI have, in most cases, limited their focus to yaw plane head rotations. Similarly, studies examining head rotation kinematics during dynamic tasks in other vestibular-impaired populations have primarily focused on yaw plane directed head movements 5,15,17,28. Our findings extend the results of these studies by confirming that head velocity alterations are not plane specific and may share a common mechanism.…”
Section: Discussionsupporting
confidence: 83%
“…Custom written algorithms (MATLAB, Mathworks, Natick, Massachusetts) were used to derive the primary outcomes from the IMU data. 26 First, sensors were corrected for alignment based on a static 3-second period at the beginning of each trial. Raw data were filtered using a 6-Hz low-pass filter.…”
Section: Instrumentation Data Reduction and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations are consistent with previous findings that healthy people have a greater head-trunk correlation than people with unilateral vestibular hypofunction while walking on a treadmill because the vestibular system controls movements of the head and trunk together through the vestibulocervical reflex and vestibulospinal reflex, respectively [40]. In people with vestibular system impairment, the head and trunk tend to move independently because they are controlled by other signals, such as visual signals and somatosensory information, respectively [41]. All participants in the present study were healthy without vestibular function impairment; they showed similar patterns of movement between the head and trunk.…”
Section: Pairwise Correlations Between Head Angle and Angles Of Other Jointssupporting
confidence: 92%
“…All outcomes were derived from sensor data using previously documented algorithms with demonstrated reliability and responsiveness. 15 In brief, the algorithms determined head turns by numerical integration of gyroscopic velocity data between the period when rotational speed exceeded 3 times the expected noise value of the signal and when the rotational speed dropped below the relevant expected noise value or the rotational velocity changed sign. For each valid head turn, head rotation amplitude was determined by the area under the curve (AUC) of the signal obtained from the head sensor, whereas head rotation velocity was determined as the maximum velocity value obtained from the head sensor.…”
Section: Methodsmentioning
confidence: 99%